Urgensi Pendirian Koperasi Syariah di Desa Rancagong Tangerang: Perspektif Analisis SWOT - Martavevi Azwar; Didi Suardi; Siti Aisyah Rahmalia (STES Islamic Village, 2021)
This research was appointed and based on the view that people are still experiencing difficulties in terms of the economy and borrowing funds whose repayment system uses high interest, and the pandemic conditions exacerbate this. In Islam this is known as usury which is hated by Allah SWT, therefore there must be a sharia financial institution that is a place for people to borrow to help their economic problems. The people of Rancagong Village, Legok Sub-district today are still making loan transactions to moneylenders with a 4:6 system, they are forced to borrow from moneylenders because there is no Sharia Cooperative that can become a forum for economic problems in the village. This study focuses on the opportunities for establishing a sharia cooperative in Rancagong Village and SWOT analysis of Sharia cooperatives. The types of this research are: field research (Field Research) with a qualitative descriptive approach and using SWOT matrix analysis. The main data sources of this research are experts on sharia cooperatives, village officials and the people of Rancagong Village.